Case report: Concomitant EGFR mutation and ALK rearrangement in non-small cell lung cancer - Hu, Haoyue; Tan, Songtao; Xie, Meng; Guo, Peng; Yu, Qiang; Xiao, Juan; Zhao, Kangrui; Liao, Qiong; Wang, Yi (Frontiers in Pharmacology, 2023)
In non-small cell lung cancer (NSCLC), two key genetic alterations, epidermal growth factor receptor (EGFR) mutations and anaplastic lymphoma kinase (ALK) rearrangements, are commonly believed to be mutually exclusive. Studies have reported that concurrent EGFR/ALK co-mutation in NSCLC patients is rare, with a prevalence ranging from 0.1% to 1.6%. However, the clinical and pathological characteristics of these patients are not well-defined, and the optimal treatment approach for such cases remains controversial. In this report, we present a case of stage IV lung adenocarcinoma with both EGFR and ALK mutations, along with high PD-L1 expression. The patient initially received treatment with EGFR tyrosine kinase inhibitors (TKIs), but the disease progressed. However, following a switch to ALK-TKI therapy and local radiotherapy, the lesion showed regression. Our report also provides a comprehensive summary of the clinical and pathological features, as well as treatment strategies, for NSCLC patients with concurrent EGFR mutation and ALK rearrangement.